Structural behaviour of composite beams with cold formed steel section - Ahmed Bamaga, Saleh Omar (2013)
The use of composite beam in buildings has known to be more economical compared to bare steel beams with hot-rolled steel section, as the composite action between steel and concrete results in significant savings in steel weight and reduce the beam depth. However, the use of composite beam with cold-formed steel of lipped C-channel is yet to be established as the structural behavior of such beam is not well understood. This study presents and discusses the behavior of composite beam with cold formed steel section and innovative shear connectors. The composite beam comprises two cold formed steel of lipped C-sections oriented back to back to form I-steel beam and perpendicular metal decking concrete slab. Three types of bracket shear connectors namely single bracket (SBSC), double bracket (DBSC) and hot rolled plate (HPSC) shear connectors were developed and used; the proposed shear connectors were fixed to the web of steel beam by bolts. In addition, headed stud (HSSC) shear connector welded to the top flange of cold formed steel beam was also investigated. Push tests in accordance with Eurocode 4 were carried out to determine the strength capacity and ductility of the proposed shear connectors. Sequentially, full-scale beam tests were conducted to investigate the actual behavior of the composite beam with the proposed shear connectors. The length of full-scale specimen between supports is 4000 mm. Theoretical validation for the experimental results was performed based on the plastic analysis of composite beam. The experimental results of push tests showed very good strength with extreme deformation capacity for all bracket shear connectors suggesting that they are strong and ductile enough to provide composite action between steel beam and concrete slab. Also, it was observed that strength capacity of shear connector increases as the thickness of steel beam increases. For headed stud shear connectors, the stud possess strength capacity as high as its predicted strength. The results of full-scale beam tests showed very good agreement as compared to theoretical values that predicted based on push test results. The bending resistance and stiffness of the composite beams were improved up to 170% and 270% respectively as compared to non-composite cold formed steel beam. Composite beam with HSSC shear connectors showed the best performance as compared to composite beams with SBSC, DBSC and HPSC shear connectors. Also, the results showed that the bending resistance of the composite beam increases as the thickness of steel beam increases. It is concluded that the proposed composite beams with cold formed steel section are strong enough to be used in small and medium size buildings.